PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF THINK-TALK-WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP KELAS VII BERDASARKAN GENDER - Hidayat, Wahyu; Sari, Novia Rahma; Agustina, Sopia; Rahayu, Elfia Sri; Saepudin, Rusli Cahya; Yunita, Winda (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The aims of this research is to know the influence of cooperative learning think-talk-write (TTW) to students' mathematics communication skill. This research was conducted on one group that is class VII-C in MTs Negeri 1 Kota Cimahi. This research method used pre-experimental one group pretest-posttest design. Analysis of this research data using paired sample T-test and independent sample test T-test. The results of this research are 1) the significant influence of cooperative learning TTW on mathematics communication skill of male students and female students, 2) no difference between the achievement of mathematics communication skill of male students with the achievement of mathematics communication skill female students.